Fiqh Munakahat Review on Divorce Caused by Parental Interference in Padang Lawas District - Pahrur Rozi Hasibuan; Sahmiar Pulungan; Fatimah Zahara (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
Marriage is an act ordered by Allah and also recommended by the Prophet. Household stability and continuity of life between husband and wife are the main goals of marriage and this is very much taken into account by Islamic law. Carrying out married life does not require the possibility of divisions and disputes that cause the condition of the household to experience disharmony. It is phenomenal that more involvement by parents in the household will lead to dependency problems which always involve the parents and are not discussed beforehand between husband and wife, the existence of the family can sometimes be a problem in the household. So the relationship between in-laws and daughters-in-law often becomes a thorny relationship. This case will be studied from the Fiqh Munakahat legal review. Divorce based on the wishes of parents that occurs in the Padang Lawas community is not valid, because there are conditions and harmony that are not fulfilled. The will and willingness to carry out an action are the basis for taklif.